2014
DOI: 10.1007/s13277-013-1570-9
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and promoter hypermethylation in colorectal cancer in India

Abstract: Microsatellite instability (MSI) is an important factor in tumor development and is a hypermutable phenotype caused by the loss of DNA mismatch repair activity. It is important to identify tumors with microsatellite instability as the patients have a better prognosis and differ with response to chemotherapy. Limited data are available on the incidence of MSI in Indian colorectal cancers (CRCs). The objectives of this study were to identify the extent of MSI in Indian CRC patients below 50 years and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…MMR protein loss is more commonly seen in right sided tumours compared to left sided and rectal tumours as was evident in this series as well. This is similar to studies from other parts of the world, [24][25][26]29 however, Ravikanth et al 30 reported MSI-H status to be present most commonly in rectal cancer (66%).…”
Section: Discussionsupporting
confidence: 88%
“…MMR protein loss is more commonly seen in right sided tumours compared to left sided and rectal tumours as was evident in this series as well. This is similar to studies from other parts of the world, [24][25][26]29 however, Ravikanth et al 30 reported MSI-H status to be present most commonly in rectal cancer (66%).…”
Section: Discussionsupporting
confidence: 88%
“…Pioneer studies in Southern India, conducted by a centre in the provincial state of Tamil Nadu, showed that 67% of cases had deficient MMR [13]. This was supported by higher prevalence rates in other studies from the state of Andhra Pradesh [14,15]. In our population in the state of Kerala, deficient MMR was found in 27% of Stage II CRC [16].…”
Section: Introductionsupporting
confidence: 80%
“…Irrespective of the pathways involved in the pathogenesis of early or late-onset CRC, MSI was found to be around 40% in another study conducted in Andhra Pradesh 17 . More recent studies from the same region showed 48% of cases were MSI 18 . There have been not many studies conducted in India to address the reason behind the high prevalence of MMR deficiency occurring in India compared to other populations.…”
Section: Introductionmentioning
confidence: 84%